Fishing at Arapus-Mangaasi, Efate, Vanuatu (2800–2200 BP): New methodological approaches and results. (April 2018) - Bouffandeau, Laurie; Béarez, Philippe; Bedford, Stuart; Valentin, Frédérique; Spriggs, Matthew; Nolet, Émilie
Abstract: The Arapus-Mangaasi site, located on the north-west coast of the island of Efate, Vanuatu, and first settled around 2800 BP, was excavated between 1999 and 2003 within the framework of a joint Australian National University-Vanuatu National Museum research and training program. The site yielded not only a range of cultural material that allowed the re-interpretation of the Central Vanuatu ceramic sequence but also well-preserved faunal remains, including a substantial number of fish bones. The present study focuses on the analysis of the ichthyofauna recovered in the area of Arapus and on the assessment of the most efficient identification protocol with a view to obtain precise faunal data leading to the characterisation of the fishing economy. Out of a total of 8080 fish remains, 2387 were taxonomically identified. The general assemblage is composed of 23 families of marine fishes, belonging to the Teleostei and Elasmobranchii groups, and dominated by surgeonfishes (Acanthuridae), parrotfishes (Scaridae), and groupers (Serranidae). The study of vertebrae allowed the identification of most acanthurids and hence proved to be essential in obtaining a detailed inventory of the fish spectrum. The assemblage composition highlights the presence of a large variety of inshore and reef-associated taxa, likely to have been caught by means of polyvalent and broad-spectrum fishing gear, possibly mass capturing devices, such as nets or traps, combined with angling and/or spearing. The results also suggest an opportunistic exploitation of ichthyofaunal resources during the Arapus period (2800 BP) and a probable decrease in the consumption of fish from the beginning of the Erueti period (2800–2200 BP) onwards. Highlights: The study deals with the analysis of archaeological fishbones from a site in Vanuatu. All of the anatomical elements have been included in the identification protocol. The assemblage is composed of 23 fish families and dominated by Acanthuridae. Exploitation of marine resources was opportunist at the time of initial settlement. Several fishing techniques could have been used in the immediate vicinity of the site.